2001
DOI: 10.1177/088840640102400105
|View full text |Cite
|
Sign up to set email alerts
|

Professional Ethics Within the Context of Student Discipline and Diversity

Abstract: Students who differ from the mainstream, both physically and culturally often find themselves at odds with the culture of schools. Under these conditions, issues of misperceptions and proportionality become paramount. With the heightened anxiety over school safety and the advent of "zero tolerance" regulations, the possibility of unethical and unfair practices for students from poor and minority groups increase considerably. These more regimented and severe policies mean that schools have an even greater oblig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…As this occurs, there is an increasing number of students, specifically students of colour, who are being jettisoned out of the educative process. Researchers (Black 2004;Cartledge, Tillman, and Johnson 2001;Casella 2003;Keleher 2000;Mosca and Hollister 2004) have consistently found that students of colour tend to be negatively affected when school systems implement zero tolerance policies. When students are suspended from school at a high rate, their chances of dropping out of school increase exponentially (McCray and Beachum 2006).…”
Section: Introductionmentioning
confidence: 97%
“…As this occurs, there is an increasing number of students, specifically students of colour, who are being jettisoned out of the educative process. Researchers (Black 2004;Cartledge, Tillman, and Johnson 2001;Casella 2003;Keleher 2000;Mosca and Hollister 2004) have consistently found that students of colour tend to be negatively affected when school systems implement zero tolerance policies. When students are suspended from school at a high rate, their chances of dropping out of school increase exponentially (McCray and Beachum 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Kunjufu (2005) indicates only 41% of African American male students in the general school population graduate from high school nationwide while only 27% of those African American males identified as special education students graduate from high school. Recent literature suggests the disparate proportions of African American males struggling academically is linked to sociopolitical issues within school contexts such as exclusionary disciplinary practices (Cartledge et al 2001;Townsend 2000), cultural differences (Cooper and Jordan 2003;Maag 2001;Vavrus and Cole 2002), or subjectively implemented zero-tolerance policies (Cooper and Jordan 2003;McFadden et al 1992;McGinnis 2003).…”
mentioning
confidence: 98%
“…The growing number of student offences over time may be indicative that a system that focuses solely on deterring offences through punishment alone may not be completely effective. Increasingly, there are calls for the holistic management of student offences in educational institutions in the UK and USA [4] [5] [6] [7]. As with some universities like the University of Nottingham [8] [9] [10], which has developed their adjudication process to adopt a sympathetic view of students who have been incarcerated for criminal offences, NUS intends to eventually incorporate more holistic programmes as part of the disciplinary process.…”
Section: Greater Emphasis On Rehabilitationmentioning
confidence: 99%